النموذج المؤسساتي الأفضل للتمكين الاقتصادي لفقراء المسلمين من خلال التمويل الأصغر دراسة مقارنة بين مختلف مؤسسات التمويل الأصغر التقليدية والإسلامية-: The best institutional model for economic empowerment of poor Muslims through microfinance - A comparative study of various traditional and Islamic MFIs- - قسول أمين; بلقلة براهيم (Journal of North African Economies, 2025)
A study by the Consultative Group to Assist the Poor (CGAP) indicates that about 650 million Muslims in the world live on less than two dollars a day, in addition, the vast majority of Muslims insist or prefer to have Sharia-compliant financial products. And after providing financial services to the poor was restricted to non-profit organizations for a long time, over the past few decades, many innovative institutions have emerged that provide financial services for the poor and low-income people around the world by commercial means , however, the question here is which of these institutional models could be the most appropriate model for serving the poor and low-income people, and achieve economic empowerment for poor Muslims? This is what we tried to answer through this study.